Addition of Ecoenzymes to Artificial Feed Formulations to Increase Survival Rate, Growth And Feed Efficiency of Climbing Perch Fish (Anabas testudineus Bloch) - Pahmi Ansyari; Noor Arida Fauzana; Slamat Slamat (Jurnal Impresi Indonesia, 2025)
Climbing perch fish (Anabas testudineus Bloch) is a high-value species in Indonesia, but its cultivation faces challenges like low survival rate and growth in early stages. Ecoenzymes, fermented organic solutions rich in amylase, protease, and lipase, offer potential to enhance feed efficiency. This study evaluated the effects of ecoenzyme-supplemented feed (0–15 ml/kg) on climbing perch fish growth, survival rate, and feed conversion ratio (FCR). A 30-day trial used a Complete Random Design (4 treatments, 3 replicates) with ecoenzyme doses of 0 (control), 5, 10, and 15 ml/kg feed. Parameters included survival rate, relative weight growth, and FCR. The 15 ml/kg dose significantly improved weight growth (229.3%) compared to control (193.7%) (p < 0.05), but survival (90–95%) and FCR (1.55–1.60) were unaffected. Ecoenzymes at 15 ml/kg enhance climbing perch fish growth, likely via nutrient digestibility. Future research should explore higher doses (>15 ml/kg), long-term effects, and ecoenzyme’s bioactive components for aquaculture sustainability.